Motivasi Santri dalam Menghafal Al-Qur'an Berdasarkan Teori Abraham Maslow di Pondok Pesantren Nurul - Dinil Khusnah Islamia; Ali Rif'an (STAI Ma'had Aly Al-Hikam Malang, 2025)
To achieve successful learning, there are several components that need to be considered, one of which is motivation. Motivation is one of the essential components needed to achieve desired outcomes. The same applies to memorizing the Qur'an. Many theories from several experts address the concept of motivation, such as the well-known Abraham Maslow's Hierarchy of Needs. This theory leans towards the content and process of learning, but fundamentally, it focuses on education and the ideal form of the learning process. This study aims to answer the following questions: (1) How is the analysis of the motivational needs hierarchy of students based on Abraham Maslow's theory in memorizing the Qur'an at Pondok Pesantren Nurul Furqon 3 Malang? (2) What are the implications of the students' motivation in memorizing the Qur'an at Pondok Pesantren Nurul Furqon 3 Malang? This research uses a qualitative descriptive approach with the research location at Pondok Pesantren Nurul Furqon 3 Malang. The research instrument is the researcher themselves, with data collection techniques through observation, interviews, and documentation. The data is analyzed using data condensation, data presentation, and conclusion drawing techniques. The process of data verification is done through source triangulation and technique triangulation. The results of this study show that the students at Pondok Pesantren Nurul Furqon 3 have various kinds of motivations. Some are intrinsic, driven by their own will, while others are extrinsic, influenced by external factors. However, when applied according to Abraham Maslow's hierarchy of needs, not all levels of needs must necessarily be fulfilled, although in the end, they will ultimately reach the peak, which is self-actualization.